2021
DOI: 10.3389/fphar.2021.681724
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MIF Associated With Disease Severity and Clinical Response of Sublingual Immunotherapy in House Dust Mite–Induced Allergic Rhinitis

Abstract: Background: Macrophage migration inhibitory factor (MIF) is described as a pro-inflammatory cytokine involved in many inflammatory and allergic disorders, but the role of MIF in allergic rhinitis (AR) remains poorly clarified. The aim of this study was to investigate the association between circulating MIF levels and house dust mite (HDM)-induced AR, and evaluate MIF as a potential biomarker in reflecting disease severity and predicting the clinical response of sublingual immunotherapy (SLIT) in HDM-induced AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In addition, MIF regulates glucocorticoid immunosuppressive effects (Leng et al, 2009) and supports and enhances macrophage proinflammatory functions by preventing p53-mediated apoptosis (Roger et al, 2001). These findings explain how MIF plays an important role in the pathogenesis of several inflammatory disorders, such as sepsis (Pohl et al, 2017), inflammatory bowel disease (IBD) (Nishihira and Mitsuyama, 2009), allergic (Xie et al, 2021) rheumatoid arthritis and lupus (Bilsborrow et al, 2019). Moreover, MIF is also involved in the protection of several parasitic infections (Rosado Jde and Rodriguez-Sosa, 2011;Filbey et al, 2019), such as Taenia crassiceps (Rodriguez-Sosa et al, 2003), Toxoplasma gondii (Terrazas et al, 2010), and Trypanosoma cruzi (Fu et al, 2012a).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, MIF regulates glucocorticoid immunosuppressive effects (Leng et al, 2009) and supports and enhances macrophage proinflammatory functions by preventing p53-mediated apoptosis (Roger et al, 2001). These findings explain how MIF plays an important role in the pathogenesis of several inflammatory disorders, such as sepsis (Pohl et al, 2017), inflammatory bowel disease (IBD) (Nishihira and Mitsuyama, 2009), allergic (Xie et al, 2021) rheumatoid arthritis and lupus (Bilsborrow et al, 2019). Moreover, MIF is also involved in the protection of several parasitic infections (Rosado Jde and Rodriguez-Sosa, 2011;Filbey et al, 2019), such as Taenia crassiceps (Rodriguez-Sosa et al, 2003), Toxoplasma gondii (Terrazas et al, 2010), and Trypanosoma cruzi (Fu et al, 2012a).…”
Section: Introductionmentioning
confidence: 96%
“…The leptin concentration in serum and nasal lavage was significantly decreased after SLIT treatment in 40 HDM-AR patients without obesity [ 129 ]. The macrophage migration inhibitory factor (MIF) is a T-lymphocyte-derived protein and the serum concentrations of MIFs were significantly lower in HDM-induced AR patient’s good-response sublingual AIT group than in the poor-response group [ 130 ].…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%
“…MIF is a pleotropic molecule that exerts a proinflammatory activity on several diseases such as sepsis, esophagitis, cancer, infections, and allergies [11][12][13][14][15][16][17]. Clinical studies demonstrated that asthmatic patients present higher MIF concentrations in the BALF, sputum, and serum than healthy controls [9,14].…”
Section: Introductionmentioning
confidence: 99%